Will Markets Direct Investments Under The Kyoto Protocol ? - Larson, Donald F. (The World Bank, 2007)
Under the Kyoto Protocol, countries can meet treaty obligations by investing in projects that reduce or sequester greenhouse gases elsewhere. Prior to ratification, treaty participants agreed to launch country-based pilot projects, referred to collectively as Activities Implemented Jointly (AIJ), to test novel aspects of the project-related provisions. Relying on a 10-year history of projects, the authors investigate the determinants of AIJ investment. Their findings suggest that national political objectives and possibly deeper cultural ties influenced project selection. This characterization differs from the market-based assumptions that underlie well-known estimates of cost-savings related to the Protocol's flexibility mechanisms. The authors conclude that if approaches developed under the AIJ programs to approve projects are retained, benefits from Kyoto's flexibility provisions will be less than those widely anticipated